DOES ESG AFFECT FIRM PERFORMANCE? EVIDENCE FROM INDONESIA - Hesniati Hesniati; Richard Richard; Yandi Suprapto; Tony Candra (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study analyzes how Environmental, Social, and Governance (ESG) affects the value of companies listed on the Indonesia Stock Exchange (IDX). Researchers applied a purposive sampling method to select 86 companies that had a clear ESG score from Refinitiv and were listed on the IDX during the 2018–2022 period. It employs Ordinary Least Squares (OLS) for data analysis, to examine the relationships between the variables. Findings show that environmental and governance performance are negatively related to firm value, this tells that companies with high environmental and governance performance will has a higher spendings which will lower the company’s value, while social performance has a positive impact when considered alongside the other ESG components. A key limitation of this study is its exclusive focus on the Indonesian market, where distinctive regulatory frameworks, ESG disclosure practices, cultural factors, and investor preferences may shape the relationship between ESG performance and firm value in ways that differ from other countries, thereby limiting the extent to which the findings can be generalized to broader global contexts.